2017
DOI: 10.1101/176099
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epstein-Barr virus nuclear antigen EBNA-LP is essential for transforming naive B cells, and facilitates recruitment of transcription factors to the viral genome

Abstract: . CC-BY-NC-ND 4.0 International license It is made available under a (which was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.The copyright holder for this preprint . http://dx.doi.org/10.1101/176099 doi: bioRxiv preprint first posted online Genetic analysis of EBNA-LP function host factors EBF1 and RBPJ to all latency promoters tested was severely delayed, 39 whereas these same factors were recruited efficiently to several host genes, some… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 87 publications
(125 reference statements)
0
10
0
Order By: Relevance
“…It is not formally possible to say whether the EBNA-LP produced in HB9 LCLs is truncated or not. However, we have found that deletion of the Y exons from the B95-8 BAC (in the context of heterogeneous IR1) results in very low protein levels ( 49 ), suggesting that any truncated EBNA-LP made may not be stable. Nevertheless, we have observed that the MVs in B95-8 do appear to have a detrimental impact on its transforming ability.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…It is not formally possible to say whether the EBNA-LP produced in HB9 LCLs is truncated or not. However, we have found that deletion of the Y exons from the B95-8 BAC (in the context of heterogeneous IR1) results in very low protein levels ( 49 ), suggesting that any truncated EBNA-LP made may not be stable. Nevertheless, we have observed that the MVs in B95-8 do appear to have a detrimental impact on its transforming ability.…”
Section: Discussionmentioning
confidence: 88%
“…The y axis shows the cell count, and the x axis shows the log 10 CellTrace Violet fluorescence intensity. The left plot is for CD19 + (gated) live cells infected as mixed lymphocytes, and the right plot is for CD19-purified B cells infected and grown in the absence of other cells, based on data also published elsewhere ( 49 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations